Competition network as a source of competitive advantage: the dynamic capability perspective and evidence from China - Wang, Liang (Lucas); Gao, Yan (2020)
The search for competitive advantage is the defining inquiry of strategic management research. In this study, we draw on the dynamic capability lens to develop a counterintuitive view that positions competitors of a firm as an important source of competitive advantage. We argue that a firm's competitors form a competition network from which it can collect information about innovative ideas, product market, and related industries. Such information helps it calibrate market opportunities, update the resource base, and, eventually, strengthen its competitive advantage. This positive effect of competition network on competitive advantage will reasonably be contingent upon the proactive information search by the firm. The empirical results based on the survey data of 631 Chinese firms strongly support our theoretical model. This study identifies another distinctive source of competitive advantage than industry context or organizational resources as well as advancing our understanding of competition network.